Nature of Radiative Recombination Processes in Layered Heterogeneous PbCdI2 Thick Films: Promising Scintillator Materials - Anatolii P. Bukivskii; Yuriy P. Gnatenko; Yuri P. Piryatinski; Igor V. Fesych; Vasyl V. Lendel; Vasyl M. Tkach; Petro M. Bukivskij (Advances in Condensed Matter Physics)
For the first time, PbCdI2 alloys in the form of thick films were prepared on a glass substrate using the conventional one-step chemical deposition method. The studies of the structural properties of these films showed that they have a very complex crystal structure, where PbI2 microcrystallites of micron and submicron sizes, as well as small nanoclusters (NCLs), are randomly formed in the CdI2 crystal matrix. It was found that the films show intense photo- and cathodoluminescence at room temperature. The temperature dependence of PL spectra of thick PbCdI2 films was studied. The nature of various radiative recombination processes in PbCdI2 films was established and it was shown that their PL spectra at room temperature are equally determined both by surface states in small PbI2 NCLs and by intrinsic defects in microcrystallites. The obtained PbCdI2 thick films can be considered as novel promising semiconductor materials for the development of effective inexpensive scintillator detectors for biomedical and industrial applications.